Computer-Assisted Cognitive-Behavioral Therapy to Treat Adolescents With Depression in Primary Health Care Centers in Santiago, Chile: A Randomized Controlled Trial - Martínez, Vania; Rojas, Graciela; Martínez, Pablo; Gaete, Jorge; Zitko, Pedro; Vöhringer, Paul A.; Araya, Ricardo (Frontiers in Psychiatry, 2019)
Introduction: Evidence from developed countries shows the efficacy of computer-assisted cognitive-behavioral therapy (cCBT) in addressing adolescent depression in home and/or school settings. This paper presents the results of a randomized controlled trial (RCT) of a brief therapist-guided cCBT intervention for adolescent depression in resource-constrained primary health care (PHC) settings. Material and methods: A multicenter, two-arm parallel-group, individually RCT with a 1:1 allocation ratio, assigned 216 depressed adolescents (aged 15-19) attending four PHC centers in a low-income municipality of Santiago, Chile, to receive eight weekly face-to-face therapist-guided cCBT sessions by study therapists (N=108), or to receive an enhanced usual care (EUC) intervention by trained PHC psychologists, encouraged to adhere to the national clinical guidelines for the management of depression (N=108). Both groups received pharmacotherapy concordant with these guidelines. The primary outcome was the Beck Depression Inventory (BDI) at four months post-randomization, to assess depressive symptoms. BDI at six months post-randomization was a secondary outcome. Additional measures included patients’ compliance, and satisfaction with different treatment components, at six-months post-randomization. Main Results: The adjusted difference in mean BDI score between groups was -3.75 (95% CI -6.23 to -1.28; p=0.003) at four months post-randomization. At six-months post-randomization, the adjusted difference in mean BDI score between groups was -2.31 (95% CI -4.89 to 0.27; p=0.078). The effect size was small-to-medium at four months post-randomization, d=0.39 (0.12 to 0.67), and small and non-significant at six months post-randomization d=0.29 (-0.00 to 0.59). Adolescents in the experimental treatment group were significantly more satisfied with treatment, with the PHC centers’ facilities, with the psychological care received, and with non-professional staff than those in the comparator treatment group. Discussion: A brief therapist-guided cCBT eight-session intervention improves the response of depressed adolescents attending PHC centers at four months post-randomization. At six months post-randomization, the differences between-groups were not significant. Future research may focus on exploring strategies to sustain and increase response. Clinical trial registration: Clinical trial unique identifier: NCT01862913; and URL: https://clinicaltrials.gov/ct2/show/NCT01862913.